A Review on Fast Dissolving Oral Films - R, Karthik D; Keerthy, H.S.; Yadav, Rajkumar Prasad (Asian Journal of Pharmaceutical Research and Development, 2021)
Oral route are the most convenient and common route of administration of drug because of the low cost of therapy and ease of administration lead to high levels of patient compliance as in the form of tablets and capsules. Generally In some cases, the oral solid dosage form may become difficult especially in swallowing. So to overcome these problems, fast dissolving drug delivery systems have been developed which disintegrate or dissolve within one minute when placed in the mouth without water or chewing. These are the formulations administered without water. These thin sized oral film stripes are designed in such a manner for the ease administration of drug when film is placed on or under the tongue. These film enables the drug to deliver directly in to the blood stream either through buccal or sublingually. Oral films improve the onset of action, lower the dosing and enhance the bioavailability.